Penilaian Kriteria Prasarana Bandar Udara Internasional dalam Mendukung Peningkatan Kunjungan Pariwisata [Criteria Assessment on the Facilities of International Airport in Supporting the Increasing Tourist Visit] - Yarlina, Lita (Warta Penelitian Perhubungan, 2018)
Tourism industry is one of the leading industries in the foreign exchange earnings for the national development. Due to the increase of tourism potential, tourism sector requires the supporting infrastructure for the accessibility. The tourist accessibility particularly the international tourists can be facilitated by considering the provision of international airport. This study aims to analyze and evaluate the provision of the airport international facility. The data collection methods were carried out by using in-depth interview with the organizer of the airport and through analysis and evaluation on the indicators and benchmarks for upgrading the status from domestic to international. The indicators which are used to upgrade the status to be the international airport are the demand of air transport services, national concerns, tourism potential, industry, trade, the integration of intermodal and multimoda transportation, and the local economy potential. The result of analysis and evaluation on the provision of airport infrastructure that have been currently surveyed is fairly adequate to be developed to be the international airport. It can be seen from the current condition showing the development stages of the facilities, such as runway, apron, and the flight safety conducted by the airport organizer. The main factor to upgrade the status to be the international airport is that it supports the tourism sector especially as the tourist attraction (domestic and international) towards the destination.Keywords: Airport Status Upgrade, Criteria Analysis, International Airport, Tourism Visiting. Sektor pariwisata merupakan salah satu sektor unggulan dalam penerimaan devisa negara untuk pembangunan nasional. Sebagai akibat dari meningkatnya potensi pariwisata, sektor pariwisata membutuhkan dukungan infrastruktur untuk aksesibilitasnya. Aksesibilitas wisatawan khususnya wisatawan mancanegara dapat dipermudah dengan mempertimbangkan penyediaan bandar udara internasional. Kajian ini bertujuan untuk menganalisis dan mengevaluasi penyediaan prasarana bandar udara internasional. Metode pengumpulan data dilakukan melalui in depth-interview kepada penyelenggara bandar udara dan melalui analisis dan evaluasi terhadap indikator dan tolok ukur peningkatan status bandar udara dari domestik menjadi internasional. Indikator yang digunakan untuk meningkatkan status menjadi bandara udara internasional adalah permintaan jasa angkutan udara, kepentingan nasional, potensi pariwisata, industri, perdagangan, keterpaduan inter dan antarmoda, dan potensi ekonomi daerah. Hasil analisis dan evaluasi penyediaan prasarana bandar udara yang disurvei saat ini sudah cukup memadai untuk dikembangkan menjadi bandar udara internasional. Hal ini dilihat dari kondisi terkini dan tahapan pembangunan terhadap fasilitas runway, taxiway, apron, dan fasilitas keselamatan penerbangan yang dilakukan oleh penyelenggara bandar udara. Faktor yang menjadi pengungkit untuk menjadi bandar udara internasional adalah sebagai penunjang sektor pariwisata sebagai daya tarik kunjungan wisatawan (domestik dan internasional) ke lokasi tujuan.Kata kunci: Peningkatan Status Bandar Udara, Analisis Kriteria, Bandar Udara Internasional, Kunjungan Pariwisata.